MRI based quantification of abscesses following experimental S. aureus intravenous challenge: application to vaccine evaluation. - Allen, E; Van Diemen, P; Yamaguchi, Y; Lindemann, C; Soilleux, E; Rollier, C; Hill, F; Schneider, J; Wyllie, D (Public Library of Science, 2016)
Purpose: To develop and validate a sensitive and specific method of abscess enumeration and quantification in a preclinical model of Staphylococcus aureus infection. Methods: S. aureus infected murine kidneys were fixed in paraformaldehyde, impregnated with gadolinium, and embedded in agar blocks which were imaged with a 9.4T MRI scanner. Image analysis techniques were developed which could identify and quantify abscesses. The result of this imaging was compared with histological examination. The impact of a S. aureus Sortase A vaccination regime was assessed using the technique. Results: Up to 32 murine kidneys could be imaged in a single MRI run, yielding images with voxels of about 25m3. S. aureus abscesses could be readily identified in blinded analyses of the kidneys after 3 days of infection, with low inter-observer variability. Comparison with histological sections shows a striking correlation between the two techniques: all presumptive abscesses identified by MRI were confirmed histologically, and histology identified no abscesses not evident on MRI. In view of this, simulations were performed assuming both MRI reconstruction and histology examining all sections of the tissue were fully sensitive and specific at abscess detection. This simulation showed that MRI provided more sensitive and precise estimates of abscess numbers and volume than histology unless at least 5 histological sections are taken through the long axis of the kidney. We used the MRI technique described to investigate the impact of a S. aureus Sortase A vaccine. Conclusion: Post mortem MRI scanning of large batches of fixed organs has application in the preclinical assessment of S. aureus vaccines.